Comparison of fundamental positive-sequence detectors for highly distorted and unbalanced systems - Pregitzer, Ricardo G. (2005)
This paper presents a performance comparison between a PLL and an Adaptive Filter for detecting the positive sequence at the fundamental frequency of any given voltage or current signals of a three-phase system. The comparative analysis was based on the evaluation of a series of steady state performance parameters (phase and amplitude errors, THD and unbalance) and on the response time. The tests were made to study the behaviour of both approaches when working with highly distorted and unbalanced signals. This work was carried out using the computer simulation tool PSCAD/EMTDC.